Theories of Employee Performance and Motivation in relation to a selected Manufacturing Industry (International Journal of Food and Nutritional Sciences, 2023)
Besides ensuring that employee motivation aligns with the company's objectives, management plays a critical role in assisting people to find more rewarding and enjoyable jobs. This is a difficult task because so many different types of people work in modern businesses. A variety of factors, including the various cultures to which people belong, influence what people value and find satisfying. From the perspective manager's perspective of a manager, this study attempts to understand what influences people, what motivates them, and why they continue to engage in certain behaviors. The motivational states of the organization's employees will be examined as part of this research. To achieve the organization's goals, a highly effective programme technique for employee motivation is required. Employee motivation programmes that are effective will help not only this organization, but all organizations, realize their full potential and create positive workplace cultures as they achieve their goals. To achieve its objectives, a company must provide its employees with the motivation and encouragement they require to succeed in their professional endeavors. Employee motivation is affected by factors that are extrinsic as well as intrinsic. This particular manufacturing company appears to be experiencing employee motivation issues for a variety of reasons, which has hampered customer satisfaction and on-time delivery of goods and services. The purpose of this research is to identify the factors that influence motivation and the relationship between motivation and job performance. Employee motivation and performance have been found to be significantly influenced by a positive work environment, the opportunity to gain valuable experience, the alignment of employees' skills and tasks, and benefit packages. Based on extensive observation following the implementation of motivational techniques, it was clear that motivated employees contributed to organizational efficiency and were critical in successfully reducing the issue of late deliveries and increasing customer satisfaction. These findings were the primary findings of this study.